V.3 - "Hovland, Carl I." (Princeton, 1949)
The present volume is the third of a series describing the wor of the Research Branch of the Army's Information and Educa tion Division. The function of the Research Branch as a whole described in Chapter 1 of the first volume. Briefly, the Branch" mission was to collect and analyze data on soldiers' attitudes anc opinions. These data, obtained primarily through anonymous questionnaires answered by enlisted men, were for general use by Army policy makers-particularly by those responsible for plan ning the information, orientation, and education programs. Much of the work of the Research Branch consisted of large-scale cross sectional surveys, carried out by the Survey Section of the Branch. Other studies, involving controlled experimentation, were the pri mary responsibility of the Experimental Section. A number of these experimental studies, dealing with the effectiveness of films and other mass-communication devices, are described in the present volume. The studies reported here are the ones thought to be of general interest to persons concerned with the use of mass-commu nication methods and those engaged in research on the effectiveness of these media.
Keywords: Sociology